ÜBER DAS PARÖMISCHE MINIMUM DES UNGARISCHEN - Forgács, Tamás (Proverbium - Yearbook, 2014)
This paper deals with the issues of paremiological minimum with special attention on why the results of German and Hungarian surveys (Grzybek 1991 and Litovkina 1993, 1996, respectively) are remarkably different. It points out that the differences are partially due to the different treatment of “common knowledge” (95% vs. 90%), but the higher scores in the Hungarian surveys may also come from the fact that Litovkina’s list is longer with more proverbs to complete. On the other hand, it has to be noted that Litovkina’s list and conclusions, despite their high value as pioneering work, have some problems. Several proverbs which are in fact each other’s variants, are listed as different items, and also some of her proverbs are somewhat archaic, missing from all the largest electronic corpora. All of the above indicate that it is time to carry out a new survey with a test list validated by previous corpus analyses.